House dust mite control measures in the management of asthma: meta-analysis. Issue 7166 (24th October 1998) - Gøtzsche, Peter C; Hammarquist, Cecilia; Burr, Michael
Abstract: Objective To determine whether patients with asthma who are sensitive to mites benefit from measures designed to reduce their exposure to house dust mite antigen in the home. Design Meta-analysis of randomised trials that investigated the effects on asthma patients of chemical or physical measures to control mites, or both, in comparison with an untreated control group. All trials in any language were eligible for inclusion. Subjects Patients with bronchial asthma as diagnosed by a doctor and sensitisation to mites as determined by skin prick testing, bronchial provocation testing, or serum assays for specific IgE antibodies. Main outcome measures Number of patients whose allergic symptoms improved, improvement in asthma symptoms, improvement in peak expiratory flow rate. Outcomes measured on different scales were combined using the standardised effect size method (the difference in effect was divided by the standard deviation of the measurements). Results 23 studies were included in the meta-analysis; 6 studies used chemical methods to reduce exposure to mites, 13 used physical methods, and 4 used a combination. Altogether, 41/113 patients exposed to treatment interventions improved compared with 38/117 in the control groups (odds ratio 1.20,  95% confidence interval 0.66 to 2.18). The standardised mean difference for improvement in asthma symptoms was −0.06 (95% confidence interval −0.54 to 0.41). For peak flow rate measured in the morning the standardised mean difference was −0.03 (−0.25 to 0.19). As measured in the original units this difference between the treatment and the control group corresponds to −3 l/min (95% confidence interval −25 l/min to 19 l/min). The results were similar in the subgroups of trials that reported successful reduction in exposure to mites or had long follow up times. Conclusion Current chemical and physical methods aimed at reducing exposure to allergens from house dust mites seem to be ineffective and cannot be recommended as prophylactic treatment for asthma patients sensitive to mites.